Diagnostic misdirection in posterior-onset Rasmussen's encephalitis: A case report - Rihab Ben Dhia, MD; Yasmine Saad, MD; Narjes Gouta, MD; Mariem Mhiri, MD; Mahbouba Frih-Ayed, PhD (Radiology Case Reports)
Rasmussen's encephalitis (RE) is a rare, chronic, and progressive inflammatory brain disorder, characterized by drug-resistant seizures, cognitive decline, and unihemispheric atrophy. Focal neurological deficits and focal motor seizures are typically the initial manifestations. However, we encountered an exceptionally rare case where occipital seizures were the sole presenting feature. This unusual presentation poses unique diagnostic and therapeutic challenges, stemming from its posterior seizure onset and atypical clinical profile, complicating recognition and effective management. We report the case of an 11-year-old boy with no prior medical or familial history of epilepsy. Born to nonconsanguineous parents, his prenatal, perinatal, and early developmental milestones were unremarkable. The patient exhibited normal psychomotor development until 5 years prior to presentation, when occipital drug-resistant visual seizures began. Clinical, imaging, and electrophysiological findings revealed posterior-onset seizures and unilateral hemispheric atrophy consistent with Rasmussen's encephalitis. Posterior-Onset seizures can present as the exclusive initial manifestation of Rasmussen's encephalitis. This case highlights the importance of considering this diagnosis in patients with newly diagnosed drug-resistant visual seizures particularly when accompanied by cognitive decline.